Hubungan Kelekatan Ayah dan Kontrol Diri dengan Kesejahteraan Subjektif serta Kesejahteraan Psikologis sebagai Mediator pada Mahasiswa - Muhammad Novvaliant Filsuf Tasaufi; Syarifah Naimi Anisa; Nasifah Rahmi; Audiht Jasmine Sabrina (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2021)
Every individual always faces problems, as well as undergraduate students. The problems are usually related to academic and non-academic issues which require the ability to manage and control themselves, so they are not overwhelmed by these problems. Father attachment can help undergraduate students in overcoming various kinds of problems. This study aims to examine the dynamics of these undergraduate students that focus on the relationship between fatherhood attachment and self-control in which subjective well-being (SWB) and psychological well-being (PWB) mediate among students in Yogyakarta. The subjects of this study were undergraduate students who lived in Yogyakarta (N = 245). This study uses five scales, two scales for the subjective well-being variable, one for the psychological well-being variable, one for the self-control variable and one for the fatherhood attachment variable. The scales used include (a) Satisfaction with Life Scale created by Diener et al (1985); (b) Positive and Negative Affect Scales by Watson et al (1988); (c) Ryff's Psychological Well-Being Scale developed by Ryff (1989); (d) Self-Control Scale from Tangney et al (2004); and (e) The fatherhood attachment scale developed by Armsden & Greenberg (1987). The data were then analyzed using mediation analysis techniques through the JASP application. The results showed that fatherhood attachment did not have a direct effect on self-control, but subjective well-being and psychological well-being could act as mediators of the relationship between fatherhood attachment and self-control.